The Potential Application of Chinese Medicine in Liver Diseases: A New Opportunity - Fu, Ke; Wang, Cheng; Ma, Cheng; Zhou, Honglin; Li, Yunxia (Frontiers in Pharmacology, 2021)
Abstract Liver diseases have been a common challenge for people all over the world, which threatens the quality of life and safety of hundreds of millions of patients. China is a major country with liver diseases. Metabolic associated fatty liver disease, hepatitis B virus and alcoholic liver disease are the three most common liver diseases in our country, and the number of patients with liver cancer is increasing. Therefore, finding effective drugs to treat liver disease has become an urgent task. Chinese medicine (CM) has the advantages of low cost, high safety, and various biological activities, which is an important factor for the prevention and treatment of liver diseases. This review systematically summarizes the potential of CM in the treatment of liver diseases, showing that CM can alleviate liver diseases by regulating lipid metabolism, bile acid metabolism, immune function, and intestinal flora, as well as exerting anti-liver injury, anti-oxidation, and anti-hepatitis virus effects. Among them, Keap1/Nrf2, TGF-β/SMADS, p38 MAPK, NF-κB/IκBα, NF-κB-NLRP3, PI3K/Akt, TLR4-MyD88-NF-κB and IL-6/STAT3 signaling pathways are mainly involved. In conclusion, CM is very likely to be a potential candidate for liver disease treatment based on modern phytochemistry, pharmacology, and genomeproteomics, which needs more clinical trials to further clarify its importance in the treatment of liver diseases. Key words: liver diseases, Chinese medicine, natural agents, toxicity, clinical trials, potential application